Prevalence and antimicrobial sensitivity pattern of Staphylococcus aureus isolated from clinical and subclinical mastitis in small ruminant in Besut and Setiu, Terengganu, Malaysia - Tajol Ariffin, Muhammad Faiq; Hasmadi, Nurhasnida; Chai, Min Hian; Ghazali, Mohd Faizal; Suhaili, Zarizal; Zainal Ariffin, Siti Mariam (Malaysian Society for Microbiology, 2020)
Aims: The study was carried out to investigate Staphylococcus aureus in clinical and subclinical mastitis in small ruminant and to identify the antibiotic sensitivity profiles of the isolates. Methodology and result: A total of 171 milk samples from lactating sheep and goats were collected from Besut and Setiu districts in Terengganu, Peninsular Malaysia. All animals were screened for mastitis using the California Mastitis Test (CMT). Phenotypic identification of S. aureus was determined using Gram-staining, Catalase test, Coagulase test, and Oxidase test. The genotypic identification was conducted using Polymerase Chain Reaction (PCR) to detect the nuc gene. The susceptibility of S. aureus to the antibiotic was tested by using the Kirby-Bauer method. In this study, subclinical and clinical mastitis were detected in 66/171 (39%) and 41/171 (24%) respectively. The cultures and PCR results showed that 18/39 (46%) samples (9 subclinical and 9 clinical mastitis) were positive for S. aureus. The antimicrobial susceptibility tests profiles shows 4/18 (22%) and 2/18 (11%) isolates were resistant to penicillin and tetracycline, respectively. However, all isolates were tetK and tetM negative. On the other hand, these isolates susceptible to amoxicillin, gentamicin, nitrofurantoin, oxacillin, cefoxitin, norfloxacin, chloramphenicol, amikacin, kanamycin, doxycycline and cefotaxime. Conclusion, significance and impact of study: The presence of S. aureus from milk samples of both clinical and subclinical mastitis goats indicates, potential hazard on the livestock as well as public health settings. The occurrence of penicillin and tetracycline resistance should not be undermined. Milk from mastitis samples may play an important role as potential reservoir and transmission of this pathogen in posing disease regardless of antibiotics resistance background.